Protein Losing Enteropathy After Fontan Operation: Glimpses of Clarity Through the Lifting Fog. Issue 1 (January 2020) - Rychik, Jack; Dodds, Kathryn M.; Goldberg, David; Glatz, Andrew C.; Fogel, Mark; Rossano, Joseph; Chen, Jonathan; Pinto, Erin; Ravishankar, Chitra; Rand, Elizabeth; Rome, Jonathan J.; Dori, Yoav
Fontan-associated protein losing enteropathy is a challenge to treat and is a major contributor to morbidity and mortality in patients with palliated single ventricle. Numerous strategies for management have been proposed, with confusion as to how best to stratify and implement care among the many treatments available. Medical management can be helpful in some, while novel lymphatic interventions hold potential for remission with good results. We review our institutional approach to protein losing enteropathy after Fontan operation and provide a suggested algorithm and pathway for effective care.